Cost and Reliability Analysis of a Hybrid Renewable Energy System - A Case Study on an Administration Building - Sun, Wenyuan; Tian, Cong; Jin, Yingai (MIST International Journal of Science and Technology, 2022)
Renewable energy generation systems have been developing rapidly in recent years. However, renewable energy systems have the problem of large power abandonment. In this paper, two different hybrid renewable energy systems (HRESs) have been designed for satisfying the electrical demand of a large office building in Changchun. A comparative analysis between two strategies is also presented to find out the best capacity for the proposed HRESs. The first HRES consists of solar PV, wind turbine, battery storage system (PV-WT-BATT) and load demand of 5,000 kWh/d. The second consists of solar PV, wind turbine, battery storage system, electrolyzer, hydrogen tank (PV-WT-BATT-EL-HT) and load demand of 5,000 kWh/d. The two HRESs are optimized for Net Present Cost (NPC), Levelized Cost of Energy (COE), Operating Cost and the rate of excess electricity minimization. The techno-economic analysis of the two HRESs is conducted using the HOMER Pro software platform. This study provides a complete guideline for determining the optimum component capacity to ensure costing estimation for the optimized performance of the two HRESs. MIJST, Vol. 10, December 2022: 29-35 DOI: https://doi.org/10.47981/j.mijst.10(03)2022.376(29-35)